UJI DIAGNOSTIK GENE XPERT MTB/RIF PADA PEMERIKSAAN MYCOBACTERIUM TUBERCULOSIS DI RSUD R. SYAMSUDIN SH KOTA SUKABUMI - Suryanata Kesuma; Tatang Abdullah (Poltekkes Kemenkes Kalimantan Timur (URL: http://poltekkes-kaltim.ac.id/), 2020)
Mycobacterium Tuberculosis infection is one of the endemic infectious diseases in Indonesia. The Mycobacterium Tuberculosis examination method in Indonesia uses conventional microscopic techniques. However, currently, a rapid molecular examination method has been developed, which is Gene Xpert MTB / RIF. The Clinical Laboratory of Syamsudin SH Sukabumi Regional Hospital is one of the hospitals that received a Gene Xpert MTB / RIF tool grant from the government. In the course of its use, diagnostic tests have not been conducted on this tools. The purpose of this study was diagnostic testing of Gene Xpert MTB / RIF for the examination of Mycobacterium Tuberculosis infection with sputum specimens. Diagnostic test values are calculated by making a 2x2 table. The comparison method in this study is conventional microscopic. Gene Xpert MTB / RIF the Clinical Laboratory of Syamsudin SH Sukabumi Regional Hospital, those are Sensitivity 85.3%, Specificity 100%, Positive Prediction Value 100% and Negative Prediction Value 92.3%. The conclusion of this research is the Gene Xpert MTB / RIF of The Clinical Laboratory of Syamsudin SH Sukabumi Regional Hospital is very high so that it can be used for screening and diagnostic Mycobacterium Tuberculosis infections.